Perancangan Tekstil Dengan Sumber Ide Griffin Untuk Fesyen Komunitas Solo Kick’s Up - Bagus Firman Pradana; Nanang Rizali (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2022)
This design developed Griffin as a basis for making textiles and functioned in the sneakerhead community fashion named Solo Kick’s Up, this activity was an introduction to a nature and identity, depicting the digital world while offering unique and interesting visuals. The purpose of this design is to develop an illustration design motif with popular visual art processing with consideration of the fashion function for the Solo Kick’s Up community. The method used consists of; design methods, design concepts and visualizations. The design method goes through the stages of problem analysis, problem solving strategies, data collection, testing, and determining the initial design ideas. The design concept includes the rationale for designing textiles. Visualization is the stage of visualizing the concept of a design plan.The results of this textile design are as follows: (1) Greek mythological creature Griffin as a source of textile design ideas in order to increase the value of textiles, The results of the design succeeded in making 7 textile designs. (2) The application of Griffin textile design as a community fashion produces outer fashion products that are memorable, attractive, unique and different from the others.